Pluralism and Contestation in the Interpretive History of Qur'an Surah al-Anfāl: 41 - Ummu Uswatun Labibah; Chusna Maladani; Mohammad Lutfianto (An-Nur International Journal of The Quran & Hadith, 2025)
This article investigates the enduring and multifaceted interpretive conflict surrounding the Qur’anic verse of khums (Q. 8:41), a foundational text for Islamic law, theology, and concepts of authority. This study employs a diachronic, historical-comparative analysis of a textual corpus from classical Islamic exegesis (tafsir) to contemporary scholarly and ideological works, including influential modern Indonesian commentators. The findings reveal a multi-layered evolution of interpretation. What began as a formative legal debate over the term ghanīma hardened into a fundamental Sunni-Shi'i schism rooted in competing political theologies of the Caliphate and the Imamate. Within Sunnism, a structured pluralism emerged, with the four primary legal schools issuing distinct rulings grounded in their respective hermeneutical principles. Beyond jurisprudence, the verse was also appropriated for non-legal ends: as an allegory for the soul's journey by Sufi mystics and as a tool of statecraft by the Ottoman and Safavid empires. In the modern era, thinkers from traditionalist, modernist, and Islamist backgrounds—such as Hamka, Quraish Shihab, and Sayyid Qutb—continue to reinterpret the verse in response to the challenges of the nation-state and contemporary ideologies. This research provides a comprehensive historical map of a single verse’s interpretive life, demonstrating how a sacred text functions as a dynamic mirror reflecting the evolution of Islamic law, identity, and thought from the classical age to the present day.